Governance of family firms (2015)
We review what the financial economics literature has to say about the unique ways in which the following three classic agency problems manifest themselves in family firms: (a) shareholders versus managers, (b) controlling (family) shareholders versus noncontrolling shareholders, and (c) shareholders versus creditors. We also call attention to a fourth agency problem that is unique to family firms: the conflict of interest between family shareholders and the family at large, which can be thought of as the “superprincipal” in a multi-tier agency structure akin to those found in other concentrated ownership structures in which the controlling owner is the state, a bank, a corporation, or other institutions. We then discuss the solutions or corporate governance mechanisms that have been devised to address these problems and what research has taught us about these mechanisms' effectiveness at solving these four conflicts in family firms.